Toward a living architecture? : complexism and biology in generative design - Cogdell, Christina (University of Minnesota Press, 2018)
Toward a Living Architecture? examines the emerging field of generative architecture and its nexus with computation, biology, and complexity. Based on Christina Cogdell's field research in architecture studios and biological labs, this book critiques generative architecture by evaluating its scientific rhetoric and disjunction from actual scientific theory and practice, definitively explaining the role of the natural sciences within contemporary architecture.